Performance of 16s rDNA Primer Pairs in the Study of Rhizosphere and Endosphere Bacterial Microbiomes in Metabarcoding Studies - Beckers, Bram; Op De Beeck, Michiel; Thijs, Sofie; Truyens, Sascha; Weyens, Nele; Boerjan, Wout; Vangronsveld, Jaco (Frontiers in Microbiology, 2016)
Next-generation sequencing technologies (e.g. 454 pyrosequencing) have revolutionized the methods for studying microbial ecology by enabling high-resolution community profiling. However, the use of these technologies in unravelling the plant microbiome remains challenging. Many bacterial 16S rRNA primer pairs also exhibit high affinity for non-target rRNA such as plastid (mostly chloroplast) rRNA and mitochondrial rRNA. Therefore, we experimentally tested a series of commonly used primers for the analysis of plant-associated bacterial communities using 454 pyrosequencing. We evaluated the performance of all selected primer pairs in the study of the bacterial microbiomes present in the rhizosphere soil, root, stem and leaf endosphere of field-grown poplar trees (Populus tremula x Populus alba) based on (a) co-amplification of non-target rRNA, (b) low amplification efficiency for pure chloroplast DNA (real-time PCR), (c) high retrieval of bacterial 16S rRNA, (d) high operational taxonomic unit (OTU) richness and Simpson Diversity and (e) taxonomic assignment of reads. Results indicate that experimental evaluation of primers provide valuable information that could contribute in the selection of suitable primer pairs for 16S rRNA metabarcoding studies in plant-microbiota research. Furthermore, we show that primer pair 799F-1391R outperforms all other primer pairs in our study in the elimination of non-target rRNA and retrieval of bacterial OTUs.